Robust design of piezoelectric actuators for structural control - Sunar, M.; Hyder, S.J.; Yilbas, B.S. (Computer methods in applied mechanics and engineering, 2001)
A robust design methodology is presented for the control of flexible structures by the use of piezoelectric actuators. The finite element modeling and analysis of the piezoelectric media are carried out via Hamilton's principle. Finite element equations are utilized for the piezoelectric control of flexible structures subject to dynamic disturbances. Various configurations of piezoelectric actuator pairs mounted on cantilever beam structures are considered for illustration purposes. The dimensions as well as the locations of the actuator pairs are assumed to be design variables varying within certain limits. Taguchi methodology is employed to these piezoelectrically controlled structures as a robust design technique in order to investigate the effects of the design variables on the control performance. Within the ranges considered in this study, it is concluded that the piezoelectric actuator pairs with larger sizes usually perform better in attenuating the structural vibrations. For the actuator pair location, the actuator pairs close to the fixed end result in better performance characteristics.